Influence Participation Compilation Budget On Managerial Performance With Commitment Organization and Motivation Work As Variables Moderation - Yudi, Yudi; Hady Octama, Ghaly Naufal; Wijaya , Rico (Jurnal Cakrawala Akuntansi, 2024)
This study aims to examine the effect of budget participation on managerial performance, with organizational commitment and work motivation serving as moderating variables. The respondents in this study consist of middle- and lower-level managers in sub-district offices located in Jambi City, particularly those with below-average IKU (Key Performance Indicator) values. A total of 54 questionnaires were distributed, from which 40 valid responses were obtained for data analysis. The study employs multiple linear regression analysis using SPSS version 22.0 to test the hypotheses.The findings reveal that budget participation has a significant positive influence on managerial performance in sub-district offices in Jambi City. Furthermore, work motivation is found to moderate the relationship between budget participation and managerial performance. However, organizational commitment does not significantly moderate this relationship.The study contributes to the literature by highlighting the conditional effects of individual psychological factors—particularly motivation—on the effectiveness of participatory budgeting in improving managerial performance. These insights are especially relevant for public sector institutions striving to enhance organizational efficiency and accountability through inclusive budgeting practices.